2018
DOI: 10.1186/s12950-018-0198-3
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the inflammasome to inflammaging

Abstract: BackgroundInflammation is a natural part of the aging process. This process is referred to as inflammaging. Inflammaging has been associated with deleterious outcomes in the aging brain in diseases such as Alzheimer’s disease and Parkinson’s disease. The inflammasome is a multi-protein complex of the innate immune response involved in the activation of caspase-1 and the processing of the inflammatory cytokines interleukin (IL)-1β and IL-18. We have previously shown that the inflammasome plays a role in the agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 46 publications
3
72
0
1
Order By: Relevance
“…IC100 was quantified in brain, spinal cord, liver and spleen at 35 days post-induction (dpi) of EAE using a proprietary assay developed by InflamaCORE, LLC using Meso Scale Technology. Protein lysates were obtained as described in [29]. The assay was read using the QuickPlex SQ 120 instrument (Meso Scale Diagnostics, Maryland).…”
Section: Quantification Of Ic100 In Tissuesmentioning
confidence: 99%
“…IC100 was quantified in brain, spinal cord, liver and spleen at 35 days post-induction (dpi) of EAE using a proprietary assay developed by InflamaCORE, LLC using Meso Scale Technology. Protein lysates were obtained as described in [29]. The assay was read using the QuickPlex SQ 120 instrument (Meso Scale Diagnostics, Maryland).…”
Section: Quantification Of Ic100 In Tissuesmentioning
confidence: 99%
“…Treatment of activated NHEKS with botanically‐derived blends of known anti‐inflammatory or antioxidant ingredients could potentially inhibit the expression of active Caspase‐1, thereby potentially retarding the inflammaging process as described by Mejias . Using 60 mJ cm −2 of UVB radiation and 5 mM ATP as the activators for active Caspase‐1 release in NHEKs, various extracellular treatments using naturally derived botanical blends were examined to see whether the ingredients could inhibit the expression of active Caspase‐1.…”
Section: Resultsmentioning
confidence: 99%
“…Essentially, it is suggested that, while it is essential for the body to respond to exogenous threats with inflammation, continuous or repeated upregulation of the inflammation response leads to accelerated ageing, including ageing of the skin. In the work reported by Mejias et al, they were able to examine fibroblasts isolated from the same individual at ages 49, 52 and 64 years. The studies demonstrated that: (i) ageing cells accumulate markers of inflammasome activation including ACS protein and active Caspase‐1 and (ii) that reduction of these markers via treatments with a known Caspase‐1 inhibitor, Ac‐YVAD‐CMK, after oxidative stress demonstrated that ‘inhibition of the inflammasome in the ageing process has the potential to treat the cellular damage associated with oxidative stress.’ This study directly links the skin’s ageing processes with inflammasome activation in human fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasome, the efficient inflammation amplifier, was inclined to get activated in aged microglia/macrophage. Multiple components of inflammasome, including NLRC4, Caspse‐1, Caspase‐11, ASC, and IL‐1β, were found to be increased in hippocampus of aged mice . In particular, expression of NLRP3, the most studied sensor of inflammasome, was increased in senile microglia compared with their young counterparts .…”
Section: Microglia/macrophage Are Prone To Form Inflammasome In Senesmentioning
confidence: 94%
“…Multiple components of inflammasome, including NLRC4, Caspse-1, Caspase-11, ASC, and IL-1β, were found to be increased in hippocampus of aged mice. 26 In particular, expression of NLRP3, the most studied sensor of inflammasome, was increased in senile microglia compared with their young counterparts. 27 Correspondingly, spontaneous activation of Caspase-1 was detected in aged brain.…”
Section: Crog Lia /Macrophag E Are Prone To Form Infl Amma Some mentioning
confidence: 99%